Assessing the Association between Late Career Working Time Reduction and Retirement Plans. A Cross-National Comparison Using the 2012 Labour Force Survey ad hoc Module. Issue 3 (13th September 2018) - Wels, Jacques
Abstract : As public policies are focusing on retaining the ageing workforce, flexible working time arrangements in late career have gained visibility over the past decades. However, given the institutional nature of these arrangements, little is known about the extent to which older workers reduce working hours at a cross-country level. Using data from the 2012 Labour Force Survey ad hoc module, the article aims to provide estimates about the number of workers aged fifty-five to sixty-nine reducing working time in a move towards retirement (before and after the first old-age pension) and assessing, using a multilevel modelling, whether these arrangements play a role in explaining the decision to work beyond the pension age in thirty European countries. Descriptive results show important variations among countries and between genders. The multilevel model shows that the impact of working time reductions in late career varies from one country to another.